Trends of Urban Area Expansion in Ranya City (1977–2024) (Raparin Journal of Humanities (RJH), 2025)
Urban expansion since the twentieth century has emerged as a significant global phenomenon, profoundly impacting urban morphology. Ranya city, situated on the Bitwen Plain in the Kurdistan Region and surrounded by prominent mountain ranges, has undergone a remarkable transformation over the past 47 years (1977–2024). This research provides a detailed analysis of the city’s spatial expansion and morphological changes.The study aims to analyze the drivers and consequences of Ranya’s expansion over the past several decades while highlighting the associated challenges and obstacles. The research utilizes Geographic Information Systems (GIS) for spatial and morphological analysis, employing demographic data and land-use assessments for quantitative evaluation. It also draws on historical records to understand past trends and evaluate the impacts of urbanization.